Efficacy and Safety of Low-Dose Cyclophosphamide vs Mycophenolatemofetil in Patients with Lupus Nephritis: A Systemic Review andMeta-Analysis - Putu Raka Widhiarta (Indonesian Journal of Rheumatology, 2025)
Background: Lupus Nephritis is still the most leading cause of morbidityand mortality in SLE (Systemic Lupus Erythematosus). Low-dose CYC(Cyclophosphamide) regimen was effective and had a higher safety profilethan standard CYC regimen. MMF (Mycophenolate Mofetil), a selectivelymphocyte antiproliferative agent, has been shown in several studies to bea safe and effective substitute to full dose CYC. The objective of this metaanalysis was to compare the efficacy and safety of these low-dose CYC vsMMF subjects with LN (Lupus Nephritis). Methods: The authorssystematically searched CENTRAL, PubMed, and ScienceDirect from 2009to early 2024. Studies enrolled RCT (Randomized Controlled Trial), in whichpatients diagnosed with lupus nephritis were treated with low-doseintravenous CYC or oral MMF. Results: A total of 6 trials, including 787patients, were included in this meta-analysis. The analysis showed there isno different between low dose-CYC MMF and MMF. (RR 0.96 95% CI [0.96,1.27], p = 0.76, Tau2 = 0.00, Chi2 = 0.07, df =1 and I2 = 0%, p = 0.79).Conclusion: No significant difference was observed between the twotreatment regimens. Oral MMF was associated in increasing vomiting andalopecia rather than low-dose CYC. Both agents demonstrated modestefficacy. However, further research is required to definitively assess therelative effectiveness and safety in a large patient cohort.